Reprints of Rare Papers on Mollusca: Martin Lister (1678) Historiae Animalium Angliae (Continued from Sterkiana 44) - Martin Lister (Hello World!, 1972)
The four plates reprinted here are nos. 6 to 9 of the original publication of 1678. The fossils represented are mainly Mollusca but there are exceptions. For example plate 7 shows many echinoids, there are a few undoubted brachiopods on plate 8 (fig. 46 and perhaps also upper fig. 44) and other brachiopods appear on plate 9 as noted below.